Proteomic analysis of plasma membrane and tonoplast from the leaves of mangrove plant Avicennia officinalis. Issue 21 (November 2014) - Krishnamurthy, Pannaga; Tan, Xing Fei; Lim, Teck Kwang; Lim, Tit‐Meng; Kumar, Prakash P.; Loh, Chiang‐Shiong; Lin, Qingsong
<x xml:space="preserve">Abstract</x> In order to understand the salt tolerance and secretion in mangrove plant species, gel electrophoresis coupled with LC‐MS‐based proteomics was used to identify key transport proteins in the plasma membrane (PM) and tonoplast fractions of Avicennia officinalis leaves. PM and tonoplast proteins were purified using two‐aqueous‐phase partitioning and density gradient centrifugation, respectively. Forty of the 254 PM proteins and 31 of the 165 tonoplast proteins identified were predicted to have transmembrane domains. About 95% of the identified proteins could be classified based on their functions. The major classes of proteins were predicted to be involved in transport, metabolic processes, defense/stress response, and signal transduction, while a few of the proteins were predicted to be involved in other functions such as membrane trafficking. The main classes of transporter proteins identified included H+‐ATPases, ATP‐binding cassette transporters, and aquaporins, all of which could play a role in salt secretion. These data will serve as the baseline membrane proteomic dataset for Avicennia species. Further, this information can contribute to future studies on understanding the mechanism of salt tolerance in halophytes in addition to salt secretion in mangroves. All MS data have been deposited in the ProteomeXchange with identifier PXD000837 (http://proteomecentral.proteomexchange.org/dataset/PXD000837).